Analisis Pengaruh Desain Pembelajaran Berbasis Teknologi Informasi dan Persepsi Guru terhadap Hasil Belajar Sejarah Kebudayaan Islam Siswa Madrasah Tsanawiyah Islam Terpadu Bogor - Kartika, Ika; Fabianza, Iqbal; Sunasa, Arman Aria (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This article aims to analyze the influence of technology-based learning design and teachers' perceptions on the learning outcomes of Islamic Cultural History. Based on the documentation of the Learning Implementation Plan (RPP) of teachers at the Integrated Islamic Junior High School in Bogor, the RPP is in line with the curriculum format of the Independent Curriculum. Learning with the use of Information and Communication Technology (ICT) has become an urgent need and demand to enhance the effectiveness of the Islamic Religious Education learning process. Through interactive learning utilizing the internet network, the potential for creating more effective learning in the subject of Islamic Cultural History can be realized. This research aims to analyze the influence of technology-based learning and teachers' perceptions on the learning outcomes of Islamic Cultural History at the Madrasah Tsanawiyah Islam Terpadu Bogor for the academic year 2022-2023. The research method used is a quantitative research design with the Structural Equation Modeling (SEM) method and the Smart-PLS approach. The calculation results using the Smart-PLS software explain the data based on the assessment questionnaire data. The goodness-of-fit value R-Square from the SEM calculation shows that the learning outcomes of Islamic Cultural History have a value of 0.725. In the F-Square section, the Learning Design has a value of 1.401, while the Teachers' Perception has a value of 0.015.